2020
DOI: 10.2147/hiv.s236304
|View full text |Cite
|
Sign up to set email alerts
|

<p>Factors Associated with Oral Candidiasis in People Living with HIV/AIDS: A Case Control Study</p>

Abstract: Background: Oral candidiasis (OC) is the most frequent opportunistic infection of the oral cavity caused by Candida species overgrowth. A wide variety of risk factor that contributes to yeast infection especially candidiasis. It might be acting as an early marker for people living with HIV/AIDS (PLWHA). There are some risk factors for PLWHA associated OC at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 31 publications
8
34
2
4
Order By: Relevance
“…We found that increasing age (≥50 years) was significantly associated with OPC among COVID‐19 patients. In a cross‐sectional study, Suryana et al revealed that increasing age ( P = .03) was significantly identified risk factor in HIV patients 32 . Elderly patients were shown to have significantly lower activity levels of protective salivary innate defences 33 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that increasing age (≥50 years) was significantly associated with OPC among COVID‐19 patients. In a cross‐sectional study, Suryana et al revealed that increasing age ( P = .03) was significantly identified risk factor in HIV patients 32 . Elderly patients were shown to have significantly lower activity levels of protective salivary innate defences 33 .…”
Section: Discussionmentioning
confidence: 99%
“…), autoimmune diseases (Sjögren syndrome, etc. ), HIV, and primary immunodeficiencies [ 57 , 58 , 59 ].…”
Section: Clinical Manifestations Of Candidiasismentioning
confidence: 99%
“…In HIV infection/AIDS, candidosis is an early sign of immunodeficiency and can indicate the immune status and disease progression in such patients [ 59 , 60 ].…”
Section: Clinical Manifestations Of Candidiasismentioning
confidence: 99%
“…Warto jednak nadmienić, że rozpowszechnienie kandydozy jamy ustnej wśród zakażonych wirusem HIV zmniejszyło się znacząco wraz z wprowadzeniem schematów wysoce aktywnej terapii przeciwretrowirusowej. [39][40][41] Mushi i wsp. 42 donoszą o zwiększonej częstości izolacji gatunków C. non-albicans o wyższej wirulencji.…”
Section: Dyskusjaunclassified